2014
DOI: 10.1501/vetfak_0000002614
|View full text |Cite
|
Sign up to set email alerts
|

Changes in selected haematological and biochemical parameters in debeaked pheasant hens during the laying period

Abstract: Summary:Changes in selected haematological and biochemical parameters during the laying period were monitored in pheasant hens kept in a cage system. Thermal cauterization of one-third of the upper part of the beak was performed before the birds were placed in the cage at the beginning of the laying period. Randomly selected pheasant hens were sampled for haematological and biochemical analysis at the beginning of the laying period, and the same hens were subsequently sampled after 6 and 12 weeks of the laying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…However, further studies are necessary to elucidate the exact origin of this observation. It has been reported that blood parameters commonly differ in relation to incubation stage in birds (Hõrak et al, 1998;Jakubas, Wojczulanis-Jakubas & Kreft, 2008;Hrabcakova et al, 2014;Wojczulanis-Jakubas et al, 2014;Wojczulanis-Jakubas et al, 2015). However, we were unable determine the laying date of the breeding birds to discriminated between early and late incubation stage to take this into account in our analyses.…”
Section: Discussionmentioning
confidence: 90%
“…However, further studies are necessary to elucidate the exact origin of this observation. It has been reported that blood parameters commonly differ in relation to incubation stage in birds (Hõrak et al, 1998;Jakubas, Wojczulanis-Jakubas & Kreft, 2008;Hrabcakova et al, 2014;Wojczulanis-Jakubas et al, 2014;Wojczulanis-Jakubas et al, 2015). However, we were unable determine the laying date of the breeding birds to discriminated between early and late incubation stage to take this into account in our analyses.…”
Section: Discussionmentioning
confidence: 90%
“…Polysaccharides silkrose contained in the 10% of pupae powder extract was assumed can increase the number of laying quail leukocytes which were experiencing stress on the production period. According to Hrabcakova et al (2014), a lot of factors that affect the levels of leukocytes in poultry i.e., genetic (species and strains), exposure to stress (stress may be temperature, environment uncomfortable cage, handling), system maintenance, feed, production period (starter, grower, layer) and the lighting program.…”
Section: Number Of Leukocytesmentioning
confidence: 99%